One Woman in the War - Alaine Polcz (Central European University Press, 2002)
Before the publication of this book, Alaine Polcz was widely recognized as a psychologist ministering to the needs of disturbed and incurably ill children and their families, as the author of numerous articles and several books on thanatology, and as the founder of the hospice movement in Hungary. The autobiographic account of the experiences of a woman, then 19-20, in the closing months of the Second World War. When it was first published, in 1991, the book was a revelation of past horrors ...
English
Keywords: rape; Refugees; inhumanity of war; World War II